Microwave discharge electrodeless lamps (MDELs). Part IX. A novel MDEL photoreactor for the photolytic and chemical oxidation treatment of contaminated wastewaters. Issue 12 (12th October 2015) - Horikoshi, Satoshi; Tsuchida, Akihiro; Shinomiya, Tomohiro; Serpone, Nick
Abstract : A novel microwave discharge electrodeless lamp (MDEL) with enhanced performance was fabricated for the microwave-assisted remediation of wastewaters contaminated with the 2, 4-D herbicide and such microorganisms as E coli . Abstract : This article reports on the fabrication and enhanced performance of a novel microwave discharge electrodeless lamp (MDEL) consisting of a three layered cylindrical structure that was effective in the remediation of wastewater containing the 2, 4-D herbicide and the near total sterilization of bacteria-contaminated pond water ( E. coli and other microorganisms) through photolysis with the emitted vacuum-UV (185 nm) and UVC (254 nm) light from the MDEL and through chemical oxidation with reactive oxygen species (ROS) produced by the photolysis of dioxygen and air oxygen through one of the photoreactors. The flow rates of the 1.0 L contaminated waters were 0.6 and 1.2 L min −1 . The integrated UV/ROSO2 and UV/ROSair methods used to carry out the degradation of 2, 4-D and sterilization processes were more effective than either the UV method alone or the ROSO2 and ROSair methods for short time periods (5 or 8 min). At a lower flow rate, 79% of 2, 4-D was degraded by the UV/ROSO2 method and 55% by UV/ROSair after 8 min. At a faster flow rate of 1.2 L min −1, degradation of 2, 4-D in 1.0 L volume of water was 84% and 77% complete by the UV/ROSO2 and the UV/ROSair method, respectively, after 8 min of irradiation. The number of kills of E. coli bacteria was nearly quantitative (98 and 99%) by the UV/ROSO2 and UV/ROSair methods after treating the contaminated water for 5 min. The decrease of total viable microorganisms in pond water was 90% and 80% after 5 min of microwave irradiation at a flow rate of 1.2 L min −1 by the integrated methods UV/ROSO2 and UV/ROSair, respectively. The rate of flow of oxygen gas through the photoreactor impacted the extent of degradation and the related dynamics of the 2, 4-D herbicide.